Penegakan Hukum Tindak Pidana Peredaran Narkotika oleh Oknum Anggota POLRI - Budi Waljiman; Didik Suhariyanto; Ismail Ismail (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
According to Law Number 35 of 2009, narcotics are substances or drugs that come from plants or non-plants, whether synthetic or semi-synthetic, which can cause a decrease or change in consciousness, loss of sensation, reduce to eliminate pain, and can lead to addiction, which is classified into groups as attached in Law Number 35 of 2009. Narcotics abuse has become a very serious issue faced by various countries, both in developed and developing countries, and one of them is Indonesia. Indonesia, which initially served as a transit country for narcotics trade, has now been turned into a destination for operations, transactions, sales, and production by international narcotics networks. This is evidenced by the numerous fields containing marijuana plants and factories producing narcotics discovered by law enforcement agencies. The research method used is a normative juridical research type, in line with the author's intended purpose, the methodology in the design of the thesis research uses two approaches, namely the Statute Approach and the Conceptual Approach. The Statute Approach is an approach carried out by examining all laws with the concept of law. The research results show that the criminal law system against members of the police force involved in narcotics trafficking, the Criminal Code only recognizes a maximum criminal system. It must be acknowledged that the emergence of this special minimum criminal sanction aims to make people afraid to commit acts as formulated in the Psychotropic Law. Problems arise when, in a specific case, the judge feels that this special minimum criminal penalty is still very severe, and law enforcement imposes criminal sanctions specified in Law No. 35 of 2009 on members of the police force who abuse narcotics, also imposing administrative sanctions, which are sanctions imposed by the relevant institution, in accordance with the main task of the police force as stated in Article 13 letter b, namely enforcing the law. Therefore, every member of the police force is required to be able to investigate and prosecute any form of criminal activity, which would be contradictory if a member of the police force commits a criminal act, as the police force should be a role model for society in implementing the law and regulations in force.